Pengaruh Kepemimpinan Transformasional Terhadap Kualitas Pelayanan Kesehatan Melalui Kualitas Sumber Daya Manusia (SDM) dan Motivasi Kerja di Rumah Sakit Umum Daerah (RSUD) Tenriawaru Kabupaten Bone - Andi Leny Puspitasari (Institusi Agama Islam Negeri (IAIN) Bone, 2026)
This study aims to analyze the effect of transformational leadership on the quality of health care through the quality of human resources (HR) and work motivation at Tenriawaru Regional General Hospital in Bone Regency. A quantitative approach with an explanatory research design was used. The study population consisted of 290 health care workers at Tenriawaru Regional General Hospital, and a sample of 168 respondents was selected using simple random sampling. Data were collected via a questionnaire and analyzed using path analysis with SPSS version 25.0. The results indicate that the quality of healthcare services at Tenriawaru Regional General Hospital is influenced by HR quality, which is the dominant factor, with knowledge and the ability to perform tasks serving as the primary indicators. Transformational leadership was found to play a role in improving service quality through the exemplary behavior and inspirational motivation provided by leaders. Although the influence of work motivation was relatively small, its role remained significant in maintaining employee morale. The quality of human resources and work motivation functioned as intervening variables capable of mediating the relationship between transformational leadership and the quality of healthcare services. This study concludes that transformational leadership, through improvements in human resource quality and work motivation, has a significant direct and indirect impact on the quality of service at Tenriawaru Regional General Hospital in Bone Regency.